Term Dha'if Dalam Tafsir Al-Munir Karya Wahbah Az-Zuhaili (Studi Kasus Komunitas Yuk Hijrah Lampung) - Ara Nismara; Siti Badi’ah; Yoga Irawan (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2026)
This study aims to understand the meaning of the term dha’īf in the Qur’ān based on the Tafsīr Al-Munīr by Wahbah Az-Zuhaili and how this meaning is actualized and practically applied by the Yuk Hijrah Lampung Community. The term dha’īf in the Qur’ān often refers to conditions of weakness in spiritual, social, and physical dimensions that require special attention. The tafsīr method used is thematic tafsīr (maudhui), involving the collection and analysis of verses related to the term dha’īf. Primary data were obtained through observation and interviews with community members who actively undertake hijrah as a concrete response to these conditions of weakness. The study’s results show that Tafsīr Al-Munīr provides a strong theological foundation and context to understand that te term dha’īf is not only interpreted as generally weak, but can also be understood as weak in social, physical, and spiritual aspects according to the context of the Qur’ān, while the Yuk Hijrah Lampung Community actualizes this understanding through hijrah classes, sharing time, and social activities. The research concludes that the understanding and application of the term dha’īf have important social and psychological functions in motivating behavioral change and religious identity among contemporary Muslim communities.